2010
DOI: 10.3109/09513590.2010.540599
|View full text |Cite
|
Sign up to set email alerts
|

Assessing osteoporosis risk factors in Spanish menopausal women

Abstract: A high prevalence of women taking osteoporosis risk-related medication was observed in our study. There was correlation between the menopausal symptoms' degree of severity and the risk of suffering from osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…4 The mean 10-year absolute fracture risk for major and hip fractures (FRAX® tool) is displayed in the different decades of age fractures in our sample. Similar results concerning family history together with age and early onset of the menopause came from a Spanish study assessing osteoporosis risk factors in menopausal women [24]. In a case-control study of Belgrade women, the following factors were related to osteoporosis: low body weight, previous fractures, early menopause, and family history for fractures [25].…”
Section: Risk Factors For Osteoporosis and 10-year Absolute Fracture supporting
confidence: 68%
“…4 The mean 10-year absolute fracture risk for major and hip fractures (FRAX® tool) is displayed in the different decades of age fractures in our sample. Similar results concerning family history together with age and early onset of the menopause came from a Spanish study assessing osteoporosis risk factors in menopausal women [24]. In a case-control study of Belgrade women, the following factors were related to osteoporosis: low body weight, previous fractures, early menopause, and family history for fractures [25].…”
Section: Risk Factors For Osteoporosis and 10-year Absolute Fracture supporting
confidence: 68%
“…Yun Zhan and colleagues, in a study of 11,075 adults from the National Health and Nutrition Examination Survey (NHANES), suggested that BMI may be a potential factor affecting the mechanism of bone density due to socioeconomic status [3] . Previous research has shown a close relationship between the development of osteoporosis in perimenopausal women and factors such as age [4] [5] , number of childbirths [6] , family history of osteoporosis [7] , BMI [8] [9] , and regular physical exercise [10] . By including 14 factors in the logistic regression model, the results of this study align with trends observed in previous research conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…According to a cross‐sectional study in Spanish menopausal women, Martinez et al . () demonstrated that the most common diseases associated with risk of osteoporosis included chronic hepatopathy, Cushing's syndrome, hyperthyroidism, malabsorption, type I diabetes mellitus, RA, Parkinson's disease, and gastrectomy. Although neurological disabilities such as cerebral palsy may affect bone health, a correlation between neurological disabilities and osteoporosis was not found.…”
Section: Discussionmentioning
confidence: 99%